Studying waiting time in pharmacy: A strategy for improving patient satisfaction - Rika Yulia; Ruddy Hartono; Mufida Indrayanti; Nur Palestin Ayumuyas; Fauna Herawati (MethodsX, 2025)
This study analyzes waiting times for compounded and non-compounded medication services and identifies factors influencing prescription delays in public and private hospitals in Surabaya. Using a quantitative cross-sectional design, the study collects data in two phases: the first focuses on outpatients and their prescription data sheets, while the second involves pharmacists and pharmacy technicians through a questionnaire. The average waiting time for compounded prescriptions was 80 min in public hospitals and 36 min in private hospital. For non-compounded prescriptions, the averages were 64 min in public hospitals and 43 min in private hospital, with some cases as low as 28 min. These results exceed the Ministry of Health standards of 60 min for compounded drugs and 30 min for non-compounded drugs. The main factors influencing waiting times were the high workload of pharmacy staff during peak hours, the number of items in prescriptions, and insufficient pharmacy staff.Patient satisfaction in the outpatient division is associated with • Information technology, • Standard operating procedures, and • Human resources.